Comparative analysis of different tomato varieties in Borana Zone, Yabello District, Southern Ethiopia (International Journal of Irrigation and Water Management, 2023)
Tomato is one of the most important vegetable in Ethiopia as well as in the world in irrigated regions. It can be produced in a wide range of climatic conditions and many types of soils. Borana zone has potential to produce the crop, but not well done due to technical (production technology) and socioeconomic problems. Among technical problem unavailability of seeds of adapted and improved tomato varieties is the most limiting factor. Therefore, the objective of this research is to test a range of improved varieties under Borana condition to identify genotypes with relatively better performance. To this effect, four improved and recommended varieties of tomato, namely: Fetan, Melkashola, Miya and Cochoro introduced from Melkassa Agricultural Research Center and one variety called CAL-J introduced from Kenya were tried for their adaptation at Yabello under irrigation using tap water in the year 2014. The experiment was single factor (varieties) single season experiment in RCBD with three replications. Parameters like Plant height, number of primary branch, days to 50% flowering, days to first harvest, Total fruit yield (ton/ha), marketable fruit yield (ton/ha), unmarketable fruit yield (ton/ha), fruits number per plant and single fruit weight (gram) were collected and analyzed. The result showed that there was significant (P ≤ 0.05) variation among the varieties for parameters including Plant height, number of primary branch, Total fruit yield (ton/ha), marketable fruit yield (ton/ha), unmarketable fruit yield (ton/ha) and single fruit weight (gram), but there was no significant variation for parameters days to 50% flowering, days to first harvest and fruit number per plant. Variety Miya gave significantly higher marketable fruit yield (22.95 ton/ha) and higher average of single fruit weight (85.84 gram) than other varieties. The least fruit marketable yield was obtained from the variety Fetan (11.61 ton/ha). Based on the result of the experiment, Variety Miya was recommended for further popularization in Yabello district under irrigation.